Isbat Nikah Massal Pasirlangu: Langkah Nyata Mewujudkan Keluarga Sakinah - Mochamad Faizal Almaududi Aziz Dachlan; Fikfik Taufik; Muhammad Husni Abdulah Pakarti; Yudi Daryadi; Azhar Muhamad Akbar; Indra Budi Jaya; Iffah Fathiah; Hendriana Hendriana; Nur Alim; Muhammad Nur Muhajir; Afifah Nur Hamidah; Nada Siti Hasanah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Unclear marital status remains a crucial issue in Pasirlangu Village, leading to family instability and hindered access to civil rights. This community service aims to solve this problem through the implementation of mass isbat nikah. The methods used include data collection of residents with nikah sirri status, socialization of the importance of isbat nikah, and cooperation with relevant agencies for the implementation of mass isbat nikah. The results showed that the implementation of mass isbat nikah succeeded in providing legal certainty to the marital status of Pasirlangu Village residents who previously had the status of nikah sirri to become legal in religion and the State. In addition, the number of couples who have been isbatized is at least 35 couples who have been successfully isbatized in this service activity. And this program also succeeded in increasing public awareness of the importance of marriage legality as the foundation of a sakinah family and the achievement of legal certainty for all Indonesian people.